Come cambia il rapporto con la chimica e le scienze, dalle superiori all’università? Una proposta di indagine - Zappoli, Sergio; Milano, Marco (Chimica nella Scuola, 2025)
Despite growing attention towards the development of forms of orientation that effectively support the transition to tertiary training courses, there is a lack, at a national level, of investigations that shed light on the factors that decisively influence the choice of scientific studies, including “informal” cultural inputs and social influences of students. This work presents the proposal for a wide-ranging investigation, based on a survey structure, led from November 2023 to February 2024, about the perception of university students regarding the real motivations that led them to embrace a degree in the scientific field. The results, collected from a large group of students, highlight an articulated and complex picture, that suggests extending this type of investigation, refining orientation strategies and supporting teaching approaches through the first years of higher degree studies.